Elements Required for an Efficient NADP-Malic Enzyme Type C4 Photosynthesis. Issue 4 (12th February 2014) - Wang, Yu; Long, Stephen P.; Zhu, Xin-Guang
Abstract : A systems model of C4 photosynthesis facilitates studies of C4 photosynthesis to quantitatively evaluate the control of different anatomical and biochemical features over light and nitrogen use efficiencies . Abstract: C4 photosynthesis has higher light, nitrogen, and water use efficiencies than C3 photosynthesis. Although the basic anatomical, cellular, and biochemical features of C4 photosynthesis are well understood, the quantitative significance of each element of C4 photosynthesis to the high photosynthetic efficiency are not well defined. Here, we addressed this question by developing and using a systems model of C4 photosynthesis, which includes not only the Calvin-Benson cycle, starch synthesis, sucrose synthesis, C4 shuttle, and CO2 leakage, but also photorespiration and metabolite transport between the bundle sheath cells and mesophyll cells. The model effectively simulated the CO2 uptake rates, and the changes of metabolite concentrations under varied CO2 and light levels. Analyses show that triose phosphate transport and CO2 leakage can help maintain a high photosynthetic rate by balancing ATP and NADPH amounts in bundle sheath cells and mesophyll cells. Finally, we used the model to define the optimal enzyme properties and a blueprint for C4 engineering. As such, this model provides a theoretical framework for guiding C4 engineering and studying C4 photosynthesis in general.